RELATIONSHIP BETWEEN READINESS AND ANXIETY LEVEL IN ELEMENTARY SCHOOL STUDENTS FACING MENARCHE IN PADEMAWU SUB-DISTRICT, PAMEKASAN - Mega Widya Puspa Ningrum; Windhu Purnomo (Universitas Airlangga, 2020)
The signs of puberty in teenagers are including physical changes such as breast development (thelarche), pubic hair growth (pubarche) and armpits, menarche, and ovulation. Menstruation that occurs for the first time is known as menarche. Teenagers facing menarche require good preparation since anxiety and fear will likely appear. Anxiety that occurs makes teenagers experience selective attention that disrupts their concentration. Preliminary studies that have been conducted by researchers are known to have elementary school students who experience anxiety facing menarche in Pademawu (sub-district) as the subjects. This study aims to analyze the relationship between readiness and anxiety level of elementary school students facing menarche in Pademawu, Pamekasan (district). The quantitative cross-sectional study is a research design chosen by researchers. The number of research samples of 75 students was obtained through cluster random sampling. The clusters used as research samples are in different schools and the same sub-district. Multinomial logistic regression is a statistical test for analyzing data. The results of the study were 49.3 percent of students had sufficient knowledge about menarche. As many as 38.7 percents of students received family support about moderate menarche. Furthermore, 68 percent of students were not ready to face menarche, and 45.3 percent of students experienced moderate anxiety. In the statistical test results obtained a correlation value of 0.001. In this research, it is known that there is a relationship between readiness and anxiety level in dealing with menarche in elementary school students in Pademawu, Pamekasan. Family willingness and support are factors that influence respondents' anxiety in facing menarche. Parents are expected to be active in educating their daughters by providing information and motivation in dealing with menarche.